Risks of Electronic Payment Services and Their Relationship to Cybercrimes: An Applied Study on the Payment Services Sector in the Kingdom of Saudi Arabia (July to August 2024) - Dawood, Nada Mansour; Muhammad, AlFaisal AbdulHamid; Jarad, Fayez Ali (Journal of Risk and Crisis Management, 2024)
With the increasing reliance on modern technologies and the widespread adoption of electronic payment systems by many institutions and individuals, numerous security threats have emerged that may lead to cybercrimes. This study aims to analyze electronic payment services in the Kingdom of Saudi Arabia and the associated security risks, as well as to explore the factors that contribute to mitigating these risks and their relationship to cybercrimes. The study utilized questionnaires directed at employees and consumers, revealing that electronic payment services are used daily but expose users to risks such as security breaches and financial fraud. Key solutions to reduce these risks include data encryption, customer awareness, and the use of antivirus software. There is a strong correlation between these risks and cybercrimes, highlighting the necessity of enhancing security through advanced protocols and additional verification techniques to protect users.